Metode Storytelling dalam Meningkatkan Keterampilan Berbicara Bahasa Indonesia Anak Sekolah Dasar: Studi Pustaka - Diffa Yunelda; Tisa Fitrisia; Khistia Fatmiatillah; Sry Apfani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study examines the use of storytelling as a learning strategy to improve elementary school students' Indonesian speaking skills. The purpose of this study is to identify the effectiveness of storytelling in developing children's language skills through a fun, communicative, and imaginative approach. This study employed a literature review method, reviewing literature and previous research relevant to Indonesian language learning at the elementary school level. The results indicate that storytelling, whether in traditional, visual, or interactive forms, consistently improves students' pronunciation, vocabulary mastery, speaking confidence, and narrative comprehension. The use of supporting media such as animation, puppets, and pair-based activities strengthens student retention and active participation. Thus, storytelling is a suitable method for Indonesian language learning as a means to improve speaking skills and build effective communication from an early age.